(untitled) (Praxis Educativa, 2025)
This essay, in continuity with Epistemology of Care (González Burgos, 2020), proposes a political, ethical and spiritual reflection that places care as the central matrix of human practices. Through a relational approach, this work articulates notions such as reciprocity, relationality and complementarity, principles of the Andean worldview, to configure an epistemic turn towards community, plural and social justice horizons. The Epistemology(ies) of Care, in this text, expands its philosophical, aesthetic, ethical, political and pedagogical foundations, anchored in the community, peasant and popular feminisms of Abya Yala. This approach, deeply anti-capitalist, anti-patriarchal and anti-colonial, seeks to dismantle epistemic hierarchies and reconcile historically fractured dimensions such as economy and ecology, politics and spirituality, and the human and the non-human. The essay underlines the centrality of care as a political and epistemic praxis to sustain life in the face of extractivist and hegemonic logics. The Epistemologies of Care are consolidated as an open political and pedagogical project, where memory, spirituality and epistemic justice are pillars of transformation. Through a philosophical and literary style, this essay invites us to imagine other possible worlds where care is not only resistance, but also the creation of more just and plural communities, deeply connected with Pachamama and us.